Validation of the clinical frailty score (CFS) in French language - Abraham, Paul (2019)
BACKGROUND: Very old critical ill patients are a rapid expanding group. To better understand the magnitude of the challenges involved in intensive care practice for an ageing population and discuss a rational allocation of resources, healthcare practitioners need a reliable evaluation of frailty. In order to promote the adequate use of the Clinical Frailty Scale (CFS) in a wider panel of countries, we aimed to develop, validate and characterise a French (FR) version from the original English (EN) CFS. METHODS: We included participants recruited prospectively for the observational "The very old intensive care patient: A multinational prospective observation study" (VIP Study) at Geneva University Hospitals (FR speaking hospital). A FR version of the CFS was obtained by translation (EN- > FR) and back translation (FR- > EN). The final CFS-FR was then evaluated twice on the same participants with at least a 2-week interval by FR-speaking doctors and nurses. RESULTS: Inter-rater reliability was 0.87 (95%CI: 0.76-0.93) between doctors for the original CFS version and 0.76 (95%CI: 0.57-0.87) between nurses for the FR version. Inter-rater variability between doctor and nurse was 0.75 (95%CI: 0.56-0.87) for the original version, and 0.73 (95%CI: 0.52-0.85) for the FR version. Test-retest (stability) with the original vs the FR version was 0.86 (95%CI: 0.72-0.93) for doctors and 0.87 (95%CI: 0.76-0.93) for nurses. Differences between the evaluations of the CFS-EN and CSF-FR were not different from 0, with a mean difference of 0.06 (95%CI -0.24, 0.36) for the EN version and - 0.03 (95%CI -0.47, 0.41) for the FR version. Average original version ratings were slightly lower than FR version ratings, though this difference did not reach significance: -0.29 (95%CI -0.54, 0.04). CONCLUSION: In this prospective cohort of very old intensive care participants we developed and tested the basic psychometric properties (internal consistency, reproducibility) of a French version of the CFS. This manuscript provides clinically meaningful psychometric properties that have not been previously reported in any other language, including in the original EN version. The French cultural adaptation of this CFS has adequate psychometric properties for doctors or nurses to evaluate frailty in very old intensive care patients.